Parental support and student athletes graduating with honors - Francisco, Anne Marie A.; Yumul, Wally D.; Jamero, Josephine Louise F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The researchers identified different manifestations of parental support received by student athletes, categorized them into different types, and compared the different forms of parental support. They interviewed eight (8)student athletes who excel both in academics and in their chosen sport. Results of the research showed that there are different manifestations of parental support and they can be categorized into four (4):emotional, informational, appraisal and instrumental support. The findings also show that there are different ways in which the student athletes perceive and react to different types of support depending on who and how the parental support is given to them and they were further analyzed through three (3) points of comparison; maternal and paternal support, solicited and unsolicited support, and support coming from athlete and non-athlete parents.
Thesis (B.S. Family Life and Child Development)---University of the Philippines Diliman.
Keywords: College athletes; Parent and child